Transcriptome profiling shows a rapid variety-specific response in two Andigenum potato varieties under drought stress - Ponce, Olga Patricia; Torres, Yerisf; Prashar, Ankush; Buell, Robin; Lozano, Roberto; Orjeda, Gisella; Compton, Lindsey (Frontiers in Plant Science, 2022)
Potato is a drought-sensitive crop whose global sustainable production is threatened by alterations in water availability. Whilst ancestral Solanum tuberosum Andigenum landraces retain wild drought tolerance mechanisms, their molecular bases remain poorly understood. In this study, an aeroponic growth system was established to investigate drought stress responses in leaf and root of two Andigenum varieties with contrasting drought tolerance. Comparative transcriptome analysis revealed widespread differences in the response of the two varieties at early and late time points of exposure to drought stress and in the recovery after rewatering. Major differences in the response of the two varieties occurred at the early time point, suggesting the speed of response is crucial. In the leaves and roots of the tolerant variety, we observed rapid upregulation of ABA-related genes, which did not occur until later in the susceptible variety and indicated not only more effective ABA synthesis and mobilization, but more effective feedback regulation to limit detrimental effects of too much ABA. Roots of both varieties showed differential expression of genes involved in cell wall reinforcement and remodeling to maintain cell wall strength, hydration and growth under drought stress, including genes involved in lignification and wall expansion, though the response was stronger in the tolerant variety. Such changes in leaf and root may help to limit water losses in the tolerant variety, while maintaining higher rates of photosynthesis. These findings provide insights into molecular bases of drought tolerance mechanisms and pave the way for their reintroduction into modern cultivars with improved resistance to drought stress and yield stability under drought conditions.